Relationship Electronic Word of Mouth With College Image - Damayanti Damayanti; Apol Pribadi Subriadi (IPTEK Journal of Proceedings Series, 2017)
Globalization in higher education has a direct impact on competition among universities in Indonesiawhich becomes keener. The competition motivates each university to continuously improve its quality. The existence of the Internet creates electronic communications and this is the beginning of the term Electronic Word of Mouth (eWOM). Electronic word of mouth has become a phenomenon that is essential to the improvement of the image in a company / organization / institution. This study aims to identify and analyze the influence of someone’s motivation who engaged in electronic word of mouth to enhance the image of the college. This research used quantitative method by analyzing the data using Structural Equation Modeling (SEM). SEM is review the multivariate analysis of variables or using scale nominal / ratio. Research shows that people are motivated to do eWOM because positive self enhancement, to helping the company, and advice seeking. The findings suggest that eWOM positive and significant effect on the image of the college.